Novel Fruit Juice Based Nutraceutical Formulation with Probiotic and Cholesterol Reduction Properties - Nair, Ajitha S.; Dubhashi, Aparna V. (International Journal of Scientific Research in Biological Sciences, 2019)
This work encompasses the use of a sporulating probiotic culture, Brevibacillus borstelensis, to prepare a nutraceutical product with a mixed fruit juice as a carrier for the culture. Lyophilization of the formulation was carried out using different dehydrating agents, pectin, ascorbic acid, gelatin, gum Arabic and maltodextrin in specific permissible concentrations. Pectin gave the best results in terms of consistency and appearance of the nutraceutical powder, hence was used in the final formulation. The nutraceutical powder was then analysed for its shelf life, physical, chemical and nutritional profile. It was also tested for heavy metal contaminants, antibacterial activity and cholesterol reduction capability. Microbiological safety of the formulation was verified according to FSSAI manual. Encouraging results were obtained from the analyses. Lyophilization helped retain the nutrients of the fruits as well as improved the keeping quality of the formulation. The novel probiotic containing nutraceutical powder prepared could be helpful to lactose intolerant population. Its cholesterol reduction property could be beneficial to hypercholesteraemic individuals.